Endometrial osseous metaplasia in a case of abnormal uterine bleeding - Gautam, Himleena; Goswami, Alaka; Goswami, Papari; Kathar, Kamal Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Endometrial osseous metaplasia is an uncommon pathology with varied clinical symptoms. Its pathogenesis is not exactly known and has a benign course. Here we present a case of a 42-year-old female with abnormal uterine bleeding who did not respond to medical management. On ultrasonography, suspected endometrial calcification was seen. Patient opted for hysterectomy and the biopsy report showed endometrial osseous metaplasia. Thus, in this case of menometrorrhagia and dysmenorrhoea, the cause was found to be osseous metaplasia.